Media booklet improve the attitude and practice of breast self-examination as early detection of breast cancer in female students - Sumiyati Sumiyati; Anita Widiastuti; Puji Hastuti; Septerina Purwandani Winarso; Hesti Kurniasih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Breast cancer is one of the main causes of death in women in Indonesia. Early detection is very important to reduce mortality from breast cancer. Early detection as an effort to prevent cancer is important. How to prevent cancer by providing education in the treatment of cancer from an early age. Breast Self Examination (Sadari) is an early detection of breast cancer. Early detection of breast cancer needs to be done from a young age. Utilization of breast self-examination media as an important resource to increase public awareness. Lack of knowledge and practice regarding breast self-examination in female students is a problem. Utilization of breast self-examination media as an important resource to increase public awareness. This study aims to determine the effect of booklets on improving the attitude and practice of breast self-examination in female students. The design of this study used a quasi-experimental with a randomized pre-test and post-test control group design. The population of this study was 292 Level I Campus VII students and a sample of 72 respondents used cluster sampling of female students in 3 groups (without media, leaflets and booklets). Data were collected using a questionnaire instrument and observation of breast self-examination practices, with a paired test to determine differences in media use. There were significant differences regarding the knowledge, attitudes and practices of breast self-examination between before and after the booklet media intervention.There is a differencesignificant mean on attitudes and practices towards BSE by giving booklets. It is recommended to use booklet media to improve breast self-examination skills in adolescents. Abstrak: Deteksi dini sangat penting menurunkan angka kematian akibat kanker payudara. Deteksi dini sebagai upaya pencegahan kanker merupakan hal yang penting. Cara pencegahan kanker dengan cara memberikan edukasi dalam penanganan kanker sejak dini. Salah satu deteksi dini kanker payudara dengan Pemeriksaan Payudara Sendiri (Sadari). Kegiatan deteksi dini kanker payudara perlu dilakukan sejak usia remaja. Pemanfaatan media pemeriksaan payudara sendiri sebagai sumber penting untuk meningkatkan kesadaran masyarakat. Kurangnya pengetahuan dan praktik tentang pemeriksaan payudara sendiri pada mahasiswi menjadi permasalahan. Pemanfaatan media pemeriksaan payudara sendiri sebagai sumber penting untuk meningkatkan kesadaran masyarakat. penelitian ini bertujuan untuk mengetahui pengaruh booklet terhadap peningkatan sikap dan dan praktik pemeriksaan payudara sendiri pada mahasiswi. Desain penelitian ini menggunakan quasi eksperiment dengan randomized pre-test and post test control group design. Populasi penelitian ini 292 mahasisiwi Tingkat I Kampus VII dan sampel 72 responden menggunakan cluster sampling mahasisiwi dalam 3 kelompok (tanpa media, leaflet dan booklet).  Pengambilan data menggunakan instrumen kuesioner dan observasi praktik pemeriksaan payudara sendiri, dengan uji paired test untuk mengetahui perbedaan penggunaan media. Terdapat perbedaan yang bermakna tentang pengetahuan, sikap dan praktik pemeriksaan payudara sendiri antara sebelum dan sesudah dilakukan intervensi dengan media booklet. Ada perbedaan mean yang signifikan pada sikap maupun praktik terhadap BSE dengan pemberian booklet. Disarankan pemanfaatan media booklet untuk meningkatkan ketrampilan pemeriksaan payudara sendiri pada remaja.